Exploring women's perception and attitude towards antidepressant use: a cross-sectional study - Ghazwa B. Korayem; Yara Alanazi; Hanouf Alanazi; Rahaf Alkhodhairi; Shoug Alamer; Sultan M. Alshahrani; Nada A. Alsaleh (BMC, 2024)
Abstract Background The World Health Organization reports that depression affects more than 280 million people globally. Women are approximately 50% more likely to experience depression compared to men. Depression during pregnancy leads to deterioration of the mother's and the fetus's health. We aim to explore women's perceptions and attitudes toward using antidepressants and to identify the factors that influence decision-making regarding antidepressant use. Method A cross-sectional survey, employing a convenience sampling method, was conducted on a university campus in Riyadh, Saudi Arabia. The survey was developed by the investigators and validated by health practitioners. Answers were reported using a 5-point Likert scale. The responses were summed up to give a total score for each respondent. Respondents who scored above or equal 75% of the total score was considered positive perception or favorable attitude. Binary logistic regression analysis was used to identify factors influencing participants' perception and attitude toward taking antidepressants. Results A total of 991 subjects were surveyed. The majority of women had negative perceptions and favorable attitudes towards using antidepressants during pregnancy reaching 64%. While women with positive perceptions and favorable attitudes represented about 20% of the study subjects. Participants reported that social stigma, religious beliefs, and fear of addiction significantly influenced their attitudes toward antidepressant use. Conclusions This study explores women's perceptions of depression and antidepressant use, revealing that a significant proportion of Saudi women have a negative perception. The research emphasizes the need for tailored awareness programs to promote informed decision-making regarding antidepressant usage among Saudi women.